2016
DOI: 10.1186/s12944-016-0370-9
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves non-alcoholic fatty liver disease via MAPK-JNK/P38 signaling in high-fat-diet-induced obese mice

Abstract: BackgroundMelatonin can regulate lipid metabolism, increase insulin sensitivity, regulate glucose metabolism and reduce body weight. This study is aimed to determine the effects and mechanism of action of melatonin on non-alcoholic fatty liver disease (NAFLD) in high-fat-diet (HFD) induced obese mice.MethodsNAFLD was induced by HFD in C57BL/6 mice. A total of 24 mice were randomly assigned to 4 groups. Groups A and B were fed with HFD for 36 weeks while groups C and D were fed with a regular diet (RD). During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 42 publications
3
49
0
Order By: Relevance
“…Pan et al also showed the dose‐dependent effect of melatonin on lipid metabolism . The weight‐reducing effect of melatonin was controversial in the previous reports . This may be due to the difference in the route of administration and duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al also showed the dose‐dependent effect of melatonin on lipid metabolism . The weight‐reducing effect of melatonin was controversial in the previous reports . This may be due to the difference in the route of administration and duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…HFD elevated activation of apoptosis signal‐regulating kinase 1 (ASK1) and downstream signaling pathways including mitogen‐activated protein kinase kinase 3/6 (MKK3/6), MKK4/7, p38, and c‐Jun N‐terminal kinase (JNK) leading to liver damage, but melatonin ameliorated HFD‐induced liver damage by inhibiting activation of these pathways in vivo . Intragastric melatonin administration (10 mg/kg daily for 12 weeks) in another study decreased serum ALT levels, liver steatosis, proinflammatory cytokine expression including interleukin 6 (IL‐6) and tumor necrosis factor alpha (TNFα), and activation of mitogen‐activated protein kinase (MAPK), JNK, and p38 signaling pathways in HFD mice, indicating that melatonin inhibits signaling pathways associated with cytokine production, inflammation, and apoptosis . Mitochondria play a vital role in β‐oxidation of FFAs, and mitochondrial dysfunctions, such as extensive mitochondrial permeability transition pore (mPTP) opening and impaired respiratory functions, lead to excess ROS production causing apoptotic cell deaths .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…Although previous studies have already discussed that melatonin enables obesity‐induced dysmetabolism of adipose tissue and hepatic steatosis to be reversed, little focused on the regulatory efforts of melatonin on their crosstalk under HFD‐induced obese condition. Considering the close relationship between adipose tissue and liver in lipid metabolism, we hypothesize that in mice with Exos MT treatment, the improvement of hepatic steatosis may originate from melatonin which mediated the functional modifications of adipocytes, although early studies report that it directly alleviates liver metabolic disorder via several hepatocyte‐intrinsic pathways . Here, we suggest that exogenous melatonin shapes the components of adipocyte‐generated exosomes via reducing the production of resistin, which further alleviates ER stress‐induced hepatic steatosis.…”
Section: Discussionmentioning
confidence: 97%